Long-term outcomes following a diagnosis of ovarian cancer at the time of preventive oophorectomy among BRCA1 and BRCA2 mutation carriers. Issue 6 (30th April 2020) - Kotsopoulos, Joanne; Karlan, Beth; Gronwald, Jacek; Hall, Elizabeth; Moller, Pal; Tung, Nadine; Zakalik, Dana; Foulkes, William D; Rosen, Barry; Neuhausen, Susan L; Sun, Ping; Lubinksi, Jan; et al.
Abstract : Introduction: Preventive bilateral salpingo-oophorectomy is the most effective means of reducing the risk of ovarian cancer among women with an inherited BRCA1 or BRCA2 mutation. Some women are diagnosed with an invasive cancer (ovarian or fallopian tube) at the time of preventive surgery, referred to as an 'occult' cancer. The survival experience of these women is not known. Methods: We estimated the 10-year survival for 52 BRCA mutation carriers diagnosed with an occult ovarian or fallopian tube cancer at the time of preventive bilateral salpingo-oophorectomy. Results: The mean age at diagnosis was 51.6 (range 33–69) years. All were serous cancers (although 14 were missing information on histologic subtype). Of the 20 cases with information available on stage at diagnosis, 10 were stage I, 1 was stage II, and 9 were stage III (n=32 missing). After a mean of 6.8 years, 12 women died (23%). The 10-year all-cause survival was 74%. Conclusion: Although based on only 52 cases, these findings suggest a more favorable prognosis for BRCA mutation carriers diagnosed with an occult rather than incident disease.